Two-year recovery courses of physical and mental impairments, activity limitations, and participation restrictions after total knee arthroplasty among working-age patients. Issue 2 (16th January 2022) - Hylkema, Tjerk H.; Brouwer, Sandra; Stewart, Roy E.; van Beveren, Jan; Rijk, Paul C.; Brouwer, Reinoud W.; Bulstra, Sjoerd K.; Kuijer, Paul P. F. M.; Stevens, Martin
Abstract: Purpose: Total knee arthroplasty is increasingly performed on working-age individuals, but little is known about their recovery process. Therefore this study examined recovery courses of physical and mental impairments, activity limitations and participation restrictions among working-age total knee arthroplasty recipients. Associated sociodemographic and health-related factors were also evaluated. Materials and methods: A prospective study among working total knee arthroplasty patients (aged <65 years) ( n = 146). Surveys were completed preoperatively and 6 weeks and 3, 6, 12, and 24 months postoperatively. Outcomes represented domains of the International Classification of Functioning, that is, physical impairments (pain, stiffness, vitality), mental impairments (mental health, depressive symptoms), activity limitations (physical functioning), and participation restrictions (social-, work functioning, working hours). Covariates included age, gender, education, home situation, body mass index, and comorbidity. Results: Largest improvements in physical and mental impairments and activity limitations were observed until 3 months postoperatively. Participation in social roles improved early after surgery, and improvements in work participation occurred from 6 to 12 months. Older age, being male and fewer comorbidities were associated with better recovery courses. Conclusion: Working-age total knee arthroplasty patients recover soon from physical and mental impairments, activity limitations, and participation in social roles, but participation at work occurs later. Younger patients, females, and those with musculoskeletal comorbidities appear at risk for suboptimal recovery after total knee arthroplasty. Implications for rehabilitation: An increasing number of working-age patients are asking for total knee arthroplasty and have high expectations of total knee arthroplasty, in particular, to participate in the workforce again; Recovery after total knee arthroplasty (TKA) does not occur in the short term and is not limited to clinical improvements for working-age TKA recipients only, as an important part of recovery, that is, participation occurs in the long term (>6 months); Closer collaboration between occupational physicians and orthopedic surgeons might result in increased and earlier ability to work full contractual hours; Rehabilitation after TKA should focus on patients with multiple comorbidities, whereby musculoskeletal diseases may even need additional preoperative treatment to optimize outcomes and prevent work disability.